IMPLEMENTATION OF “DESA MANDIRI” CONCEPT IN THE COVID-19 PANDEMIC SITUATION (CASE STUDY DESA SUKANALU, SUBDISTRICT BARUSJAHE) (President University, 2019)
There are certain obstacles in implementing Desa Mandiri Concept since Covid-19 Pandemic enacted as global disaster. This article aims to explain the effort of village to become Independent as reflected in Desa Mandiri Concept. In order to explain its practice in the society, this article is based on the research conducted in Sukanalu Village. This research uses social legal methods, which is interdisciplinary in nature able to explain legal issues more meaningfully theoretically and practically explains the operation of law in the daily lives of citizens. The results of this study indicate that the synergy between the village government and the community will facilitate the sustainability of development in Sukanalu Village. The goals that were built from scratch will be realized. From the research findings, it can be seen that the ability of the village of Sukanalu is quite a lot, namely budget assistance from the central government through village funds, assistance from local governments, and having a reliable community for guarding posts and disseminating central government policies and area. Therefore, it can be seen that the village government's strategy through utilizing its capabilities has gone well in accordance with the prevailing policies in dealing with the Covid-19 Pandemic.Keywords: Desa Mandiri, Sukanalu Village.